Nilai Budaya Dalam Sastra Lisan Bukoba Di Rambah Hilir Rokan Hulu - Serli Putri Dwi Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2023)
Bukoba oral literature is one of the traditions that exist in Rambah Hilir, Rokan Hulu, Riau. The purpose of this research is to find out the cultural values as well as the moral message contained in the koba ratok lalageh anak rang rambah and timang anak. The method used is qualitative with data collection through observations, interviews, and documentation. The results of this study describe the culture contained in the koba ratok lalageh anak rang rambah which is to invite the community around to preserve this culture that has begun to disappear. Then the moral message contained in the koba timang anak is to do good wherever you are, so it will be easy to find friends and innocent people.